Applying design for 3R and design for disassembly method to determine the end-of-life stage of the bicycle - Mohd Suhaimi, Mustapar (2008)
Recycling is one of the popular ways to ensure that the product is environmental friendly. There are several value recovery processes, including cannibalization and remanufacturing. However, the design of most products does not favor the recovery of added value. Product designed for optimal marketing and ease of manufacturing are not necessarily good candidates for a recovery scheme. Design measure such as recyclability, disassemblability, and reusability are defined and used as the basic of the product recovery time. This project proposed a framework for design method that adopts the environmental – friendly philosophy via the concept of reuse, recycle and remanufacture. The bicycle is adopted as a case study. The expected output is the design method that considers 3R philosophy.